Scapular Osteotomy for Lateral Access to a T1-2 Foraminal Disc Extrusion, Treated by Mini-Hemilaminectomy in a Dog - Nicolas, Marie; Bureau, Stéphane; Job, Chloé; Guillemot, Alexandre (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
A 4-year-old female spayed French bulldog was presented with a 2-day history of neck pain and left thoracic limb lameness with no neurological deficits. A computed tomography (CT) examination showed a left foraminal T1-2 disc extrusion. Surgical management was performed using a left lateral approach to the vertebral column with a scapular osteotomy. A T1-2 mini-hemilaminectomy was performed. The scapular osteotomy was stabilized with two 2.4-mm locking compression plates. The postoperative CT and radiographic examinations showed adequate decompression of the T1-2 foramen and good reduction in the scapular osteotomy. The dog was able to walk the following day. At the 1-month follow-up, the dog had no neck pain but persistent slight left thoracic limb lameness. Ten months postoperatively, a CT scan showed no abnormalities at the surgical site, and the dog had no neurological deficits nor lameness. The aim of this case report was to describe a new lateral approach to T1-2 intervertebral space.
Keywords: dog; cranial thoracic disc extrusion; lateral approach; scapular osteotomy; T1-2 mini-hemilaminectomy